The Digital Transformer's Dilemma - Frankenberger, Karolin; Mayer, Hannah; Reiter, Andreas; Schmidt, Markus (Ascent Audio, 2020)
In The Digital Transformer's Dilemma: How to Energize Your Core Business While Building Disruptive Products and Services, the authors show companies how to go digital while also advancing their core business. The book emphasizes how to strike a difficult balance between establishing a new (digital) business and re-vitalizing-and digitizing-the legacy business. The core of the book is focused on the actual implementation of the digital transformation across both businesses, providing concrete tips, tricks, tools and action plans across six key dimensions: crafting a flexible organization; using technology as a driver; designing the necessary processes; building transformational leaders; "Right-skilling" the workforce of the future; and galvanizing cultural change. Based on 100+ interviews with senior executives at leading companies (such as Nestle, Novartis, Volkswagen, BNP Paribas, BASF and Michelin) and smaller hidden champions, numerous illuminating case studies, and the authors' own experience from working in international management consulting and years of academic experience, the book highlights the fundamental principles required for executives and businesspeople to transform legacy organizations into digitally empowered companies.